1997
DOI: 10.1021/jf9608837
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Potential of Potato Tubers To Synthesize Blackspot Pigments in Relation to Their Actual Blackspot Susceptibility

Abstract: In a study of six potato varieties (Solanum tuberosum L.), which were grown under two different fertilization regimes, the biochemical potential of tuber tissue to synthesize blackspot pigments was distinguished from the actual blackspot susceptibility exhibited after impact application. Blackspot susceptibility and biochemical potential for pigment synthesis were not correlated, which supports the hypothesis that the extent to which the blackspot potential is actually being used is mediated by the sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
34
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 14 publications
(23 reference statements)
8
34
1
1
Order By: Relevance
“…The observed lack of correlation between low tyrosine content and resistance to bruising indicated that substrate level does not seem to be preliminary factor playing a main role in mechanism of bruising formation. This conclusion is in agreement with results of other studies (Mondy and Munshi 1993;Stevens and Davelaar 1997;Strehmel et al 2010).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The observed lack of correlation between low tyrosine content and resistance to bruising indicated that substrate level does not seem to be preliminary factor playing a main role in mechanism of bruising formation. This conclusion is in agreement with results of other studies (Mondy and Munshi 1993;Stevens and Davelaar 1997;Strehmel et al 2010).…”
Section: Discussionsupporting
confidence: 94%
“…Mondy and Munshi (1993) studied two potato cultivars, one resistant and one susceptible to bruising, have found that tyrosine level was not a limiting factor for bruising determination, since in the susceptible cultivar they observed a lower level of tyrosine. Stevens and Davelaar (1997) have demonstrated positive correlation between potential to discoloration formation and tyrosine content, but at the same time they have not found correlation between blackspot bruise susceptibility and level of tyrosine. Strehmel and coworkers (2010) have proved that the level of tyrosine did not change significantly after mechanical impact in two tested cultivars.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Black Spot Bruise Resistance Tuber blackspot caused by impact and pressure during harvest and storage, as well as tuber tissue browning after cutting, is caused by the oxidation of phenolic compounds by the enzyme polyphenol oxidase (PPO) to quinones, which polymerize to cause dark pigmentation (Stevens and Davelaar 1997). Silencing of PPO genes in potato leads to a reduction in enzymatic browning of tuber tissue due to wounding and bruising from impact (Bachem et al 1994;Coetzer et al 2001;Chi et al 2014).…”
Section: Tuber Quality Traitsmentioning
confidence: 99%
“…Our results also indicate that backbone integration frequencies for P-DNA vectors are similar to those for conventional T-DNA vectors (data not shown). Polyphenol oxidases (PPOs) play a role in the activation of defenses against pests and pathogens (Thipyapong and Steffens, 1997) but also trigger enzymatic browning, which negatively impacts potato storage and processing quality (Stevens and Davelaar, 1997). To control enzymatic browning without impairing inducible defense mechanisms, we isolated clones from a variety of potato cDNA libraries and selected the gene that is predominantly expressed in mature tubers, weakly expressed in microtubers, not expressed in leaves, and not induced upon infection (data not shown).…”
Section: Selection Against Backbone Integrationmentioning
confidence: 99%